Les archives à l’épreuve du temps : les recadrements temporels des courts métrages de la série Souvenir - Huberman, Isabella (Canadian Journal of Film Studies, 2020)
This article examines how “colonial time” is called into question in two short films of the National Film Board of Canada’s series Souvenir, from 2015. The question of time lies at the heart of this series, for which the NFB commissioned contemporary Indigenous filmmakers to take up their archives of visual material on Indigenous peoples. The colonial temporal framework is at work in the vast archives of ethnographic and documentary film and photography on Indigenous peoples dating back to the early twentieth century, in which Indigenous people are often represented as part of “vanishing” cultures. Thus, in this article, I underscore the temporal interruptions that occur when ethnographic visual material of Indigenous peoples is put into the hands of contemporary Indigenous artists. I focus first on what it means to repurpose dehumanizing colonial archives and ask whether visual sovereignty is in fact possible within the archives. By analyzing the reappropriation of archival footage in the short films Mobilize by Caroline Monnet and Etlinisigu’niet (Bleed Down) by Jeff Barnaby, I elucidate how the filmmakers break with modes of colonial time through what I propose to call “reframings” that offer alternative ways of conceiving of time. By rehabilitating ethnographic images, these filmmakers refuse to project the material into the distant past and complicate the readability of Indigenous images in the archives, revealing how the reappropriation of old images can be just as powerful as the production of new ones.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé